Kraśkiewicz-Pragacz modules and some positivity properties of Schubert polynomials - Masaki Watanabe (Discrete Mathematics & Theoretical Computer Science, 2015)
We use the modules introduced by Kraśkiewicz and Pragacz (1987, 2004) to show some positivity propertiesof Schubert polynomials. We give a new proof to the classical fact that the product of two Schubert polynomialsis Schubert-positive, and also show a new result that the plethystic composition of a Schur function with a Schubertpolynomial is Schubert-positive. The present submission is an extended abstract on these results and the full versionof this work will be published elsewhere.